Financial management behaviour in supporting the sustainability of MSMEs in the Sarbagita region Bali - Putri, I Gusti Agung Prabandari Tri; Dwiputranti, Made Irma; Salilama, Fikri; Baswedan, Yasmin Fazilah (Goodwood Publishing, 2025)
Purpose: This study aims to analyse the role of FMB in supporting the sustainability of MSMEs. This analysis is essential because financial management among MSMEs in Bali remains suboptimal, with challenges in separating personal and business finances. Methodology/approach: Denpasar, Badung, Gianyar, and Tabanan Regency (Sarbagita) were chosen as research locations based on previous observations. The adoption of FinTech and the measurement of FinSat in achieving financial performance (FP) have been under-researched. This research was conducted quantitatively to analyse the FP of MSMEs in achieving business sustainability. Results/findings: DFL has a positive and significant influence on FMB, and FinTech has a positive and significant impact on FinSat. However, FinSat positively and significantly influences FP. FinSat mediates the relationship between FinTech and FP, but FMB does not mediate the relationship between DFL and FP. Conclusions: The implementation of Fintech helps owners achieve FinSat, thereby meeting MSME performance targets. Individuals must have DFL to mitigate the risks associated with Fintech Limitations: The research location, which is limited to only four regencies/cities in Bali, presents a limitation, making the results not generalizable to all MSMEs. Additionally, the financial management aspect of this study does not include the financial conditions of previous periods. Contribution: The research findings contribute to the development of personal financial management science and are utilized in MSME mentoring to optimize their business sustainability.